Micropollutant transformation and taxonomic composition in hybrid MBBR – A comparison of carrier-attached biofilm and suspended sludge. (1st September 2021) - Wolff, David; Helmholz, Lissa; Castronovo, Sandro; Ghattas, Ann-Kathrin; Ternes, Thomas A.; Wick, Arne
Highlights: Comparison of suspended sludge and carrier-attached biofilms from three hybrid MBBRs. Transformation rate constants and bacterial composition were investigated. Composition differences in sludge and biofilms could be attributed to 69 genera. For several micropollutants the biofilms showed a higher degradation potential. Statistical link between some abundant taxa and high transformation rates was found. Abstract: The suspended sludge and carrier-attached biofilms of three different hybrid moving bed biofilm reactor (MBBR) systems were investigated with respect to their transformation potential for a broad range of micropollutants (MPs) as well as their microbial community composition. For this purpose, laboratory-scale batch experiments were conducted with the separated suspended sludge and the carrier-attached biofilm of every system in triplicate. For all batches the removal of 31 MPs as well as the composition of the microbial community were analyzed. The carrier-attached biofilms from two hybrid MBBR systems showed a significant higher overall transformation potential in comparison to the respective suspended sludge. Especially for the MPs trimethoprim, diclofenac, mecoprop, climbazole and the human metabolite 10, 11-dihydro-10-hydroxycarbamazepine consistently higher pseudo-first-order transformation rates could be observed in all three systems. The analysis of the taxonomic composition revealed taxa showing higher relative abundances in the carrier-attached biofilms (e. g. Nitrospirae and Chloroflexi) and in the suspended biomasses (e. g. Bacteroidetes and Betaproteobacteria). Correlations of the biodiversity indices and the MP biotransformation rates resulted in significant positive associations for 11 compounds in suspended sludge, but mostly negative associations for the carrier-attached biofilms. The distinct differences in MP removal between suspended sludge and carrier-attached biofilm of the three different MBBR systems were also reflected by a statistically significant link between the occurrence of specific bacterial taxa ( Acidibacter, Nitrospira and Rhizomicrobium ) and MP transformation rates of certain MPs. Even though the identified correlations might not necessarily be of causal nature, some of the identified taxa might serve as suitable indicators for the transformation potential of suspended sludge or carrier-attached biofilms. Graphical abstract: Image, graphical abstract